Fisherfolk voices on mariculture operations in Sagñay, Camarines Sur, Philippines - Vargas, Bernadine; Cope, Mylene; Piano, Monica; De Vergara, Jepthe; Cerio, Calyd (Sustainability Science and Resources, 2024)
This study investigates the responses and perceptions of fisherfolk in Sagñay, Camarines Sur, Philippines to the Mariculture Park project, using the Triple Bottom Line (TBL) theory to assess economic, environmental, and social impacts. Employing a qualitative case study design, the research involves in-depth interviews with eight local fisherfolk from coastal barangays affected by the project. The study employs purposeful sampling to gather insights into the challenges and perceptions of participants regarding the mariculture initiative. Data was analyzed using reflexive thematic analysis (RTA), which identified key themes about the community's experience and the project’s implications. The findings highlight the need for a balanced approach that integrates economic benefits, environmental sustainability, and social cohesion to support community well-being. The study recommends strategies for aligning mariculture practices with local needs and preserving ecological balance, providing valuable guidance for policymakers and practitioners to enhance the project’s impact and address the concerns of affected fisherfolk.